Serum Levels of SDF-1 and CXCR4 in Breast Cancer: Correlation with Disease Progression and Chemotherapy Response in Iraqi Women - Noor Al Rubaiey; Hazima ALabassi (Kirkuk Journal of Science)
Breast cancer is the most frequently diagnosed cancer among women worldwide and remains a significant global health issue. Autophagy plays a dual role in breast cancer, influencing both anti-tumor immunity and tumor progression. This study aimed to investigate the role of autophagy markers, specifically SDF1 and CXCR4, in breast cancer pathogenesis among Iraqi women.A total of 90 participants, aged 25–65 years, were divided into three groups: 30 newly diagnosed breast cancer patients, 30 patients undergoing chemotherapy, and 30 healthy controls. The chemotherapy regimen for the treated group included Adriamycin (60 mg/m²) combined with cyclophosphamide, administered in 21-day cycles. Diagnosis was confirmed through mammography and histopathological examination. Blood samples (3 ml) were collected, processed, and stored for analysis, with serum levels of SDF1 and CXCR4 measured using ELISA kits.The study revealed that SDF1 levels were significantly elevated in newly diagnosed patients (84.91 ± 4.2 pg/ml) compared to chemotherapy patients (59.94 ± 2.18 pg/ml) and controls (57.00 ± 3.47 pg/ml), with p≤0.001. Similarly, CXCR4 levels were highest in newly diagnosed patients (0.5 ± 0.06 ng/ml), followed by controls (0.11 ± 0.01 ng/ml) and chemotherapy patients (0.08 ± 0.01 ng/ml), also with p≤0.001. A moderate positive correlation between SDF1 and CXCR4 (r = 0.5, p = 0.001) was observed, indicating their potential role in breast cancer progression.These findings highlight the significance of SDF1 and CXCR4 as potential markers for understanding breast cancer pathogenesis and progression, offering insights for targeted therapeutic